Gender-Dependent Association of FTO Polymorphisms with Body Mass Index in Mexicans. - Yolanda Saldaña-Alvarez; María Guadalupe Salas-Martínez; Humberto García-Ortiz; Angélica Luckie-Duque; Gustavo García-Cárdenas; Hermenegildo Vicenteño-Ayala; Emilio J Cordova; Marcelino Esparza-Aguilar; Cecilia Contreras-Cubas; Alessandra Carnevale; Margarita Chávez-Saldaña; Lorena Orozco (PLoS ONE, 2016)
To evaluate the associations between six single-nucleotide polymorphisms (SNPs) in intron 1 of FTO and body mass index (BMI), a case-control association study of 2314 unrelated Mexican-Mestizo adult subjects was performed. The association between each SNP and BMI was tested using logistic and linear regression adjusted for age, gender, and ancestry and assuming additive, recessive, and dominant effects of the minor allele. Association analysis after BMI stratification showed that all five FTO SNPs (rs1121980, rs17817449, rs3751812, rs9930506, and rs17817449), were significantly associated with obesity class II/III under an additive model (P<0.05). Interestingly, we also documented a genetic model-dependent influence of gender on the effect of FTO variants on increased BMI. Two SNPs were specifically associated in males under a dominant model, while the remainder were associated with females under additive and recessive models (P<0.05). The SNP rs9930506 showed the highest increased in obesity risk in females (odds ratio = 4.4). Linear regression using BMI as a continuous trait also revealed differential FTO SNP contributions. Homozygous individuals for the risk alleles of rs17817449, rs3751812, and rs9930506 were on average 2.18 kg/m(2) heavier than homozygous for the wild-type alleles; rs1121980 and rs8044769 showed significant but less-strong effects on BMI (1.54 kg/m(2) and 0.9 kg/m(2), respectively). Remarkably, rs9930506 also exhibited positive interactions with age and BMI in a gender-dependent manner. Women carrying the minor allele of this variant have a significant increase in BMI by year (0.42 kg/m(2), P = 1.17 x 10(-10)). Linear regression haplotype analysis under an additive model, confirmed that the TGTGC haplotype harboring all five minor alleles, increased the BMI of carriers by 2.36 kg/m(2) (P = 1.15 x 10(-5)). Our data suggest that FTO SNPs make differential contributions to obesity risk and support the hypothesis that gender differences in the mechanisms involving these variants may contribute to disease development.